1997
DOI: 10.1177/002215549704501008
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Soluble Guanylate Cyclase Activity in the Guinea Pig Cochlea Suggests Involvement in Regulation of Blood Flow and Supporting Cell Physiology

Abstract: SUMMARYAlthough the nitric oxide/cGMP pathway has many important roles in biology, studies of this system in the mammalian cochlea have focused on the first enzyme in the pathway, nitric oxide synthase (NOS). However, characterization of the NO receptor, soluble guanylate cyclase (sGC), is crucial to determine the cells targeted by NO and to develop rational hypotheses of the function of this pathway in auditory processing. In this study we characterized guinea pig cochlear sGC by determining its enzymatic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…Our own observations indicate that both calmodulin and sGC are present at moderate levels in vestibular hair cells and in nerve fibers below the sensory epithelium, as well as at higher levels in cells in the transitional epithelium and dark cell epithelium (Dhaliwal and Lysakowski, 2000). Fessenden and Schacht (1997) however, find no labeling for cGMP, the reaction product of sGC, in hair cells, but instead have found cGMP immunoreactivity in Deiter's and Hensen's supporting cells in the cochlea. Similar results for Hensen's and Claudius cells and for nerve fibers under both inner and outer hair cells have been described by .…”
Section: Possible Mechanism Of Action Of Nitric Oxide In the Vestibulmentioning
confidence: 89%
“…Our own observations indicate that both calmodulin and sGC are present at moderate levels in vestibular hair cells and in nerve fibers below the sensory epithelium, as well as at higher levels in cells in the transitional epithelium and dark cell epithelium (Dhaliwal and Lysakowski, 2000). Fessenden and Schacht (1997) however, find no labeling for cGMP, the reaction product of sGC, in hair cells, but instead have found cGMP immunoreactivity in Deiter's and Hensen's supporting cells in the cochlea. Similar results for Hensen's and Claudius cells and for nerve fibers under both inner and outer hair cells have been described by .…”
Section: Possible Mechanism Of Action Of Nitric Oxide In the Vestibulmentioning
confidence: 89%
“…The constitutive neuronal isoform of NOS is present in nerve fibers innervating inner and outer hair cells and spiral ganglion cells [23]. Soluble guanylate cyclase (sGC) and cGK were also localized in supporting structures (Deiters' cells, Hensen's cells, inner and outer pillar cells) of the organ of Corti [24,26]. Previous studies suggested that CO, arising from heme via metabolism by HO, stimulates sGC activity to promote an increase in the cGMP located in neural and cardiovascular tissues [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sGC. which is activated by NO, was found to be present, together with its second messenger cGMP, in the pericytes of capillaries in the spiral ligament and spiral prominence (21). Fessenden and Schacht (21) considered that the NOS/cGMP pathway in the pericytes may govern cell contractility by lowering levels of Ca*^"^.…”
Section: Discussionmentioning
confidence: 99%